2016
DOI: 10.1111/cmi.12683
|View full text |Cite
|
Sign up to set email alerts
|

Extrusions are phagocytosed and promoteChlamydiasurvival within macrophages

Abstract: The precise strategies that intracellular pathogens use to exit host cells have a direct impact on their ability to disseminate within a host, transmit to new hosts, and engage or avoid immune responses. The obligate intracellular bacterium Chlamydia trachomatis exits the host cell by two distinct exit strategies, lysis and extrusion. The defining characteristics of extrusions, and advantages gained by Chlamydia within this unique double‐membrane structure, are not well understood. Here, we define extrusions a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…These findings mirror our previous results in macrophages (27), indicating a similar extrusion-mediated benefit to Chlamydia during interactions with both of these cell types. A marked and provocative contrast, however, was that extrusion engulfment resulted in dramatically different host cell outcomes for DCs and macrophages.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…These findings mirror our previous results in macrophages (27), indicating a similar extrusion-mediated benefit to Chlamydia during interactions with both of these cell types. A marked and provocative contrast, however, was that extrusion engulfment resulted in dramatically different host cell outcomes for DCs and macrophages.…”
supporting
confidence: 91%
“…Chlamydia trachomatis survival in DCs is low, in contrast to the robust growth seen in its main target, the epithelial cell (26). We have previously shown that containment within extrusions increases the survival of Chlamydia in macrophages, prolonging the period during which viable bacteria can be recovered from these cells (27). As innate phagocytic cells and potent stimulators of cell-mediated adaptive immunity, DCs are likely to play a key role in generating protective host responses to Chlamydia (28, 30, 31, 33).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations